Systematic Study of Oxygen Evolution Activity and Stability on La1–xSrxFeO3−δ Perovskite Electrocatalysts in Alkaline Media - She, S.; Yu, J.; Tang, W.; Zhu, Y.; Chen, Y.; Sunarso, J.; Zhou, W.; Shao, Zongping (American Chemical Society, 2018)
Perovskite oxide is an attractive low-cost alternative catalyst for oxygen evolution reaction (OER) relative to the precious metal oxide-based electrocatalysts (IrO 2 and RuO 2 ). In this work, a series of Sr-doped La-based perovskite oxide catalysts with compositions of La 1-x Sr x FeO 3-Î´ (x = 0, 0.2, 0.5, 0.8, and 1) are synthesized and characterized. The OER-specific activities in alkaline solution increase in the order of LaFeO 3-Î´ (LF), La 0.8 Sr 0.2 FeO 3-Î´ (LSF-0.2), La 0.5 Sr 0.5 FeO 3-Î´ (LSF-0.5), SrFeO 3-Î´ (SF), and La 0.2 Sr 0.8 FeO 3-Î´ (LSF-0.8). We establish a direct correlation between the enhancement in the specific activity and the amount of surface oxygen vacancies as well as the surface Fe oxidation states. The improved specific activity for LSF-0.8 is clearly linked to the optimum amount of surface oxygen vacancies and surface Fe oxidation states. We also find that the OER performance stability is a function of the crystal structure and the deviation in the surface La and/or Sr composition(s) from their bulk stoichiometric compositions. The cubic structure and lower deviation, as is the case for LSF-0.8, led to a higher OER performance stability. These surface performance relations provide a promising guideline for constructing efficient water oxidation.